Estudio geológico-geotécnico a detalle para la construcción del parque eólico Santo Domingo Tramo I; cantón Loja provincia de Loja. - Gordillo Quizhpe, Manuel Eduardo (2013)
The main purpose of the present project is to carry out the geologic-geotechnical study of Wind Park Eólico Sto. Domingo Tramo I, which will relate the behaviors of the floors and rock in order to have very high margins of trust for the construction of this project of great importance for our county with which one of the renewable energies that are the only projects with speeds average of the winds at south America level takes advantage of 12.5 m/s and heights of 2.600 msnm and 2700msnm. The stratigraphic column of the study area is constituted by loamy floors, slimes, schists and line of the metamorphic basement of the unit Chiguinda attributed to the paleozoico of other rocks preexistentes which were subjected to big to pressures and high temperatures which modify its texture and mineralogical composition but without being carried out a coalition of the material. Tectónicamente the study place presents the following ones characteristic the flaws consider active according to the work of Egüez et to the (2003) in a radio of 200 km from Villonaco are the flaws that define the subandino and they are of the inverse type with cabalgamiento address toward the This. Such flaws are those of Santiago-Upano, Macuma and Taisha that are of address N-S and they present an inclined plan of low angle toward the West. They have also shown up earthquakes under the area of the you take care of Loja, with magnitudes of M=5 and M=6, but generally more associated to the area of coastal subduction but for reasons of conformation of badges these earthquakes have been registered with depths 87 km, Toward the west in contact with the unit Chiguinda expands the formation Sacapalca of age paleocénica which are tufas andesiticas that regionally extends toward the north of the equator. The analysis of the zonificación of the susceptibility to the processes of mass movements is the elaboration of digital thematic maps; treatment statistical univariado to determine the specific susceptibility of each variable; geo-statistical prosecution to determine the relationship of each parameter unit quantitatively with regard to the processes of mass removal; elaboration of the map algorithm to carry out the crossing of layers; and statistical multivariate treatment to obtain the map of final susceptibility.